New methods for identifying Lyman continuum leakers and reionization-epoch analogues. Issue 1 (14th August 2020) - Katz, Harley; Ďurovčíková, Dominika; Kimm, Taysun; Rosdahl, Joki; Blaizot, Jeremy; Haehnelt, Martin G; Devriendt, Julien; Slyz, Adrianne; Ellis, Richard; Laporte, Nicolas
ABSTRACT: Identifying low-redshift galaxies that emit Lyman continuum radiation (LyC leakers) is one of the primary, indirect methods of studying galaxy formation in the epoch of reionization. However, not only has it proved challenging to identify such systems, it also remains uncertain whether the low-redshift LyC leakers are truly 'analogues' of the sources that reionized the Universe. Here, we use high-resolution cosmological radiation hydrodynamics simulations to examine whether simulated galaxies in the epoch of reionization share similar emission line properties to observed LyC leakers at z ∼ 3 and z ∼ 0. We find that the simulated galaxies with high LyC escape fractions ( f esc ) often exhibit high O32 and populate the same regions of the R23–O32 plane as z ∼ 3 LyC leakers. However, we show that viewing angle, metallicity, and ionization parameter can all impact where a galaxy resides on the O32– f esc plane. Based on emission line diagnostics and how they correlate with f esc, lower metallicity LyC leakers at z ∼ 3 appear to be good analogues of reionization-era galaxies. In contrast, local [S ii ]-deficient galaxies do not overlap with the simulated high-redshift LyC leakers on the S ii Baldwin–Phillips–Terlevich (BPT) diagram; however, this diagnostic may still be useful for identifying leakers. We use our simulated galaxies to develop multiple new diagnostics to identify LyC leakers using infrared and nebular emission lines. We show that our model using only [C ii ]158 μ m and [O iii ]88 μ m can identify potential leakers from non-leakers from the local Dwarf Galaxy Survey. Finally, we apply this diagnostic to known high-redshift galaxies and find that MACS 1149_JD1 at z = 9.1 is the most likely galaxy to be actively contributing to the reionization of the Universe.